Semi-Fluid: A Content Distribution Model For Faster Dissemination Of Data - Saleh, Salah Noori (2010)
This thesis proposes and implements a novel content distribution model for reducing or minimizing delay in data dissemination. Currently, content distribution is based on two models: the Fluid model and the Chunk model. The Fluid model provides continuous transferring of the content from the source to multiple receivers. For high throughput, a receiving node should distribute a bit once it has received that bit. However, working with the Fluid model in a heterogeneous network needs special care because the model incorporates tightly coupled connections between adjacent nodes. This imposes fundamental performance limitations, such as dragging down all transfer rates in the system to the rate of the slowest receiving node. In the Chunk model, contents are first chopped into pieces of equal size and the subsequent distribution happens in pieces.